Expression of genes encoding for proteins involved in heparan sulphate and chondroitin sulphate chain synthesis and modification in normal and malignant plasma cells - Bret, Caroline; Hose, Dirk; Reme, Thierry; Sprynski, Anne-Catherine; Mahtouk, Karène; Schved, Jean-François; Quittet, Philippe; Rossi, Jean-François; Goldschmidt, Hartmut; Klein, Bernard (British journal of haematology, 2009)
Syndecan-1 is a proteoglycan that concentrates heparin-binding factors on the surface of multiple myeloma cells, and probably plays a major role in multiple myeloma biology. As heparan sulphate and chondroitin sulphate are the bioactive components of syndecan-1, we analysed the signature of genes encoding 100 proteins involved in synthesis of these chains, i.e. from precursor uptake to post-translational modifications, using Affymetrix microarrays. The expression of enzymes required for heparan sulphate and chondroitin sulphate biosynthesis was shown to increase in parallel with syndecan-1 expression, throughout the differentiation of memory B cells into plasmablasts and normal bone marrow plasma cells. Sixteen genes were significantly different between normal and malignant plasma cells, nine of these genes -EXT2, CHSY3, CSGALNACT1, HS3ST2, HS2ST1, CHST11, CSGALNACT2, HPSE, SULF2 - encode proteins involved in glycosaminoglycan chain synthesis or modifications. Kaplan-Meier analysis was performed in two independent series of patients: B4GALT7, CSGALNACT1, HS2ST1 were associated with a good prognosis whereas EXT1 was linked to a bad prognosis. This study provides an overall picture of the major genes encoding for proteins involved in heparan sulphate and chondroitin sulphate synthesis and modifications that can be implicated in normal and malignant plasma cells.
First published online 2 March 2009
Gesehen am 14.01.2022